2005
DOI: 10.1016/j.transproceed.2004.11.086
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Stable Liver Transplant Recipients From a Twice-Daily Prograf-Based Regimen to a Once-Daily Modified Release Tacrolimus-Based Regimen

Abstract: The steady-state tacrolimus exposure of MR tacrolimus once daily is equivalent to Prograf twice a day after a milligram-for-milligram conversion in stable liver transplant recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
67
2
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 3 publications
14
67
2
1
Order By: Relevance
“…Three studies reported that within-subject variability [percentage coefficient of variation (% CV)] in AUC 0-24 or C min decreased significantly following conversion from Prograf Ò to Advagraf Ò [28,35,43], while two studies could find no significant difference [31,45]. Conversion from Prograf Ò to Advagraf Ò resulted in a significant reduction in within-subject variability in tacrolimus AUC 0-24 from 14.1 to 10.9 % (but no reduction in C min ) in a study involving 40 stable kidney transplant recipients, assessed using five AUC values for each dosing regimen [28], and a reduction in tacrolimus C min from 14.0 to 8.5 % in a study involving 129 stable kidney transplant recipients [35].…”
Section: Xrmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies reported that within-subject variability [percentage coefficient of variation (% CV)] in AUC 0-24 or C min decreased significantly following conversion from Prograf Ò to Advagraf Ò [28,35,43], while two studies could find no significant difference [31,45]. Conversion from Prograf Ò to Advagraf Ò resulted in a significant reduction in within-subject variability in tacrolimus AUC 0-24 from 14.1 to 10.9 % (but no reduction in C min ) in a study involving 40 stable kidney transplant recipients, assessed using five AUC values for each dosing regimen [28], and a reduction in tacrolimus C min from 14.0 to 8.5 % in a study involving 129 stable kidney transplant recipients [35].…”
Section: Xrmentioning
confidence: 99%
“…Conversion from Prograf Ò to Advagraf Ò resulted in a significant reduction in within-subject variability in tacrolimus AUC 0-24 from 14.1 to 10.9 % (but no reduction in C min ) in a study involving 40 stable kidney transplant recipients, assessed using five AUC values for each dosing regimen [28], and a reduction in tacrolimus C min from 14.0 to 8.5 % in a study involving 129 stable kidney transplant recipients [35]. Two studies reported significantly less within-subject variation in exposure after conversion to MR tacrolimus but provided no actual numerical data [43,60]. Another study reported similar within-and betweensubject variability between Prograf Ò and Advagraf Ò formulations [31].…”
Section: Xrmentioning
confidence: 99%
“…A new prolonged release formulation of tacrolimus was recently developed as a once-daily formulation (Advagraf Ò ) (First 2008;Florman et al 2005). Therapeutic regimens for transplants recipients are often complex, contributing to a high incidence of medication non compliance and as consequences an increased mortality and morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…The AUCs of tacrolimus are known to correlate highly with trough concentrations after dosing of a standard twice-daily formulation, it can easily be speculated that the AUC of tacrolimus may be associated Florman et al, 2005;Dansirikul et al, 2006;Masuda and Inui, 2006). Because AUC measurement for tacrolimus is complicated and AUC and efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…We have hypothesized that the maximal blood concentration (Cmax) of tacrolimus may be closely related to its toxicity. In addition, since there is a high correlation between the tacrolimus concentration-time area under the curve (AUC) and its trough concentration, tacrolimus concentration et al, 2005;Florman et al, 2005;Dansirikul et al, 2006;Masuda and Inui, 2006). If this hypothesis is valid, a sustainedrelease formulation would be less toxic because the Cmax would be lower.…”
Section: Introductionmentioning
confidence: 99%